2020
DOI: 10.1007/s40430-020-02311-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a highly compressible elastomeric material model to simulate compressed expanded graphite and its application in the optimization of a graphite-metallic structure

Abstract: The paper presents simulations of mechanical properties of compressed expanded graphite. To model the stress and strain states of compressed expanded graphite, a hyperelastic material model formulated by the Blatz-Ko was adapted. The idea of using this model resulted from the assumptions that compressed expanded graphite exhibits similar mechanical properties to polyurethane foam with high density. The material constant of the Blatz-Ko model was determined by numerical calculations where deformation energy equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…The deformation of the filler described by Equation (12) or (13) allows the location of the point on the compression curve ( Figure 12 ) to be determined and the derivative determining the local value of the modulus of elasticity (with a known analytical notation of the equation that models the course of the compression curve of the filler) to be calculated. In paper [ 24 ], a slightly different method of calculating this parameter was proposed, and it was shown that the modulus of elasticity is directly proportional to the area under the stress–strain curve. The modulus of elasticity (calculated in this way) is the average value from the entire deformation range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deformation of the filler described by Equation (12) or (13) allows the location of the point on the compression curve ( Figure 12 ) to be determined and the derivative determining the local value of the modulus of elasticity (with a known analytical notation of the equation that models the course of the compression curve of the filler) to be calculated. In paper [ 24 ], a slightly different method of calculating this parameter was proposed, and it was shown that the modulus of elasticity is directly proportional to the area under the stress–strain curve. The modulus of elasticity (calculated in this way) is the average value from the entire deformation range.…”
Section: Resultsmentioning
confidence: 99%
“…The modulus of elasticity (calculated in this way) is the average value from the entire deformation range. In the method presented below, the determination of the average value of the modulus of elasticity is based on the model presented in [ 24 ] but takes into account the effect of the initial compression/deflection of the material that fills the windings of the spiral gasket. If the filler is initially compressed, the area under the stress–strain curve (representing the local modulus of elasticity) will get smaller.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analyzed solution, the parameters that limit the sought area of the optimal gasket's structure were the geometrical dimensions of the core's cross-section, the strength of the used materials, as well as the ensuring of a minimum pressure exerted on the sealing surface. A similar optimization model was presented in [15]. The limitations of the gasket's dimensions were the maximum outer diameter dz = 90mm, the minimum inner diameter dw = 49mm, and the maximum height h = 10 mm.…”
Section: Formulation Of the Optimization Problemmentioning
confidence: 99%
“…Experimental and simulation results showed that these constructions have a larger effective contact area than conventional gaskets. Jaszak 34 studied the mechanical properties of compressed, expanded graphite used in bolted joint structures. The feasibility of a hyperelastic material model was developed and verified, and the connection structure was optimised.…”
Section: Introductionmentioning
confidence: 99%